Improve the quality of service through secure routing networks secured in the mail - Nadhum Kadhum, Aseil (International Journal of Engineering and Technology, 2023)
A mobile ad hoc network (MANET) is a stand-alone system with mobile nodes.  Nodes can move around at will. Communication is subject to security breaches without a centralized, secure infrastructure, and the nodes are the biggest offenders. Since security has become one of the most important issues for data transfer via wired and wireless networks, many security-enhanced solutions have been created to enhance the security of data transmission over public networks. The goal of this project is to make routing safer. Proactive routing, as is well known, involves finding alternative routes and requiring packets to choose one at random from their immediate neighbors. Sending hello packets allows us to maintain track of each node's neighbors.  The delivery path is then selected from nearby nodes, with the prior hop which is retained as the history node having been arbitrarily excluded. To randomize delivery channels, the proactive routing protocols DSDV and RDSDV were contrasted for various node counts. The Simulation employs this project. The rapid development of mobile computing appli-cations and distant systems has raised awareness of quality of service (QoS) for mobile ad hoc networks (MANETs). In the MANET sce-nario, security is a key component of Qos provisioning. Attacks on the system could result in problems with direction, asset reservations, or even the collapse of the QoS structure if no security tool is used. In this study, two new plans will be provided from the perspectives of two alternative techniques to manage the updating of the organizational idea and allay the worries caused by interface annoyances in order to handle the security challenges of MANET Qos and the actual commitments of this investigation.